2019
DOI: 10.1002/qj.3586
|View full text |Cite
|
Sign up to set email alerts
|

Does monsoon gyre always favour tropical cyclone rapid intensification?

Abstract: In this study, potential impacts of monsoon gyres (MG) on the development of a tropical cyclone (TC) are investigated using idealized numerical simulations. When a TC is embedded in an MG, our results show that its development is slower, and its intensity is weaker compared with that evolved with no background flow. We identified three MG dynamic mechanisms that can affect TC development. First, the superposition of TC and MG circulations produce a larger outer size for the TC. A TC with a larger size develops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 79 publications
(107 reference statements)
0
8
0
Order By: Relevance
“…Geetha and Balachandran (2016) discussed the role of diabatic heating during RI of TC over NIO. Yan et al (2019) showed that monsoon gyre mechanisms aAect the RI of TCs. Zhang et al (2019) have shown that when mean kinetic energy is converted into eddy kinetic energy, an increase in the diabatic heating cause the RI of TCs.…”
Section: Ri Dynamicsmentioning
confidence: 99%
“…Geetha and Balachandran (2016) discussed the role of diabatic heating during RI of TC over NIO. Yan et al (2019) showed that monsoon gyre mechanisms aAect the RI of TCs. Zhang et al (2019) have shown that when mean kinetic energy is converted into eddy kinetic energy, an increase in the diabatic heating cause the RI of TCs.…”
Section: Ri Dynamicsmentioning
confidence: 99%
“…It has been reported previously that monsoon gyres (MGs: Lander, 1994;1996;Harr et al, 1996) affect the track of TCs, which can experience sudden northward turning when they are embedded in an MG (Carr and Elsberry, 1995;Ge et al, 2018). Some studies suggested that MGs can modulate the intensity of TCs (Liang et al, 2016;2018a;2018b;Yan et al, 2019;Song et al, 2021). Based on a statistical analysis of the Joint Typhoon Warning Center (JTWC) dataset, Liang et al (2018a) and Song et al (2021) found that TCs are more likely to incur rapid weakening when they are embedded in an MG. Liang et al (2016;2018b) found that MGs affected the change in intensity of typhoon Chan-Hom (2015) by modulating the transport of mass and moisture into the TC.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a statistical analysis of the Joint Typhoon Warning Center (JTWC) dataset, Liang et al (2018a) and Song et al (2021) found that TCs are more likely to incur rapid weakening when they are embedded in an MG. Liang et al (2016;2018b) found that MGs affected the change in intensity of typhoon Chan-Hom (2015) by modulating the transport of mass and moisture into the TC. Based on an idealized numerical experiment, Yan et al (2019) found that the development of TCs is slower when they are embedded in an MG and that MGs affect the intensity of TCs through vorticity segregation processes, barotropic instability and the modulation of vertical wind shear.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that MG might weaken TC intensity by modulating TC's structure, which is consistent with their previous studies (Liang et al, 2016;Liang et al, 2018b). Based on idealized numerical experiments, Yan et al (2019) suggested that TC development in a MG could be interfered by three dynamical mechanisms, namely vorticity segregation process, barotropic instability, and VWS. Liang et al (2018a) and Wu et al (2013b) used a low-pass Lanczos filter with a 10-days cutoff to the wind fields in which the TC circulation was removed using the method of Kurihara et al (1993) and Kurihara et al (1995) to obtain a MG.…”
Section: Introductionmentioning
confidence: 99%